Run faster, bowl faster: In-match analysis of elite female cricket pace bowlers - Bailey, D.; Saw, A. E.; Crowther, R. H.; Sims, K. (The Journal of Sport and Exercise Science, 2023)
Pace bowlers who release the ball at a higher velocity have been shown to both reduce the scoring ability of batters and dismiss batters more often. Run-up velocity is a key parameter consistently shown to influence ball velocity in male pace bowlers, however this has yet to be evaluated in female pace bowlers who have different anthropometric characteristics, strength, and bowling biomechanics. The aim of this study was to analyse in-match global positioning system (GPS) unit data and ball velocity data to determine whether characteristics of the run-up and delivery stride were associated with ball velocity in elite female pace bowlers. Wearable device (gyroscope, accelerometer, and GPS) data and ball velocity data were collated from 28 elite female pace bowlers participating in a T20 competition. Linear regressions were conducted on 1050 bowling deliveries for both absolute ball velocity (raw data) and relative ball velocity (percent of individual`s maximum). Univariate analyses found absolute ball velocity was strongly associated with run-up distance (p = 0.002), average run-up velocity (p = 0.010), maximum run-up velocity (p < 0.001), maximum velocity during delivery stride (p < 0.001), peak resultant acceleration (p = 0.013), and peak roll (p = 0.031). Relative ball velocity was most strongly associated with maximum run-up velocity (p = 0.004) and maximum velocity during delivery stride (p < 0.001). Multivariate analysis found absolute ball velocity was strongly predicted by maximum velocity during delivery stride (p < 0.001), peak resultant acceleration (p = 0.003), run-up distance (p = 0.008), and peak roll (p = 0.043). Bowlers should aim to increase their run-up velocity, particularly during the delivery stride, to increase ball velocity. However, this should be in the context of individual factors such as biomechanics and strength.